An in situ study on the role of heterogeneous microstructure on anisotropic tensile deformation behaviour in an additive manufactured Ti6Al4V alloy: Data - Khadar Syed, Abdul (Cranfield University, 2024)
Additive manufacturing (AM) processes are known to produce heterogeneous microstructures and thereby, anisotropic mechanical properties. However, a fundamental understanding of the anisotropic mechanical behaviour of AM-built Ti6Al4V is limited, particularly for high-deposition-rate wire-feed directed-energy-deposition AM processes. The present study provides insights into the role of heterogenous microstructure and associated texture on the tensile deformation and damage accumulation in wire-feed directed-energy-deposition Ti6Al4V. Materials were deposited using oscillation-pass and parallel-pass build strategies. In situ neutron diffraction studies were performed on samples with tensile loading applied parallel and perpendicular to the built layers. Dissimilar thermal histories experienced in the parallel-pass strategy resulted in thinner columnar β grains and finer transformation microstructure, resulting in higher yield strength compared to the oscillation strategy. The presence of strong columnar β fibre texture in both build strategies led to anisotropic deformation. When loaded perpendicular to the columnar grains, elastic strain accumulation is more crystallographically homogeneous and includes basal, prismatic, and pyramidal plane strain accumulation in both build strategies. Conversely, when loaded parallel to the columnar β fibre texture, the majority of the pyramidal orientations preferentially aligned along the loading axis and were subjected to significant elastic strains. Similar anisotropy was observed under plastic deformation where tensile strain accumulation observed in the prismatic planes and prismatic slip is found to be the major slip activity. Such activity was not detected when loaded parallel to the columnar grains. Hence anisotropic deformation is observed in the studied material.
Keywords: 'Wire arc additive manufacturing'; 'Neutron diffraction'; 'Heterogeneous microstructure'; 'Titanium alloy'; 'Deformation behaviour'